2020
DOI: 10.35848/1347-4065/ab8f09
|View full text |Cite
|
Sign up to set email alerts
|

Nested Mach–Zehnder interferometer optical switch with phase generating couplers

Abstract: In reconfigurable optical networks, an optical switch is indispensable to afford routing optical signals without optical/electrical conversion. A nested Mach-Zehnder interferometer (MZI) optical switch is suitable for a silicon-silica hybrid structure compared with a conventional cascaded MZI switch. We proposed to employ phase generating couplers (PGCs) instead of directional couplers (DCs) in the nested MZI optical switch. Calculation results show that the nested MZI switch with PGCs exhibits <−30 dB crossta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…It was also found that crosstalks in a 2-stage nested MZI switch are further suppressed in two output ports chosen among four output ports. A 3-stage nested MZI optical switch has three output ports with low crosstalk among eight output ports [16]. In addition, we have reported that a 4-stage nested MZI switch has low crosstalk less than −40 dB over a wavelength range of as wide as 200 nm from 1450 to 1650 nm by choosing six ports among 16 output ports [18].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was also found that crosstalks in a 2-stage nested MZI switch are further suppressed in two output ports chosen among four output ports. A 3-stage nested MZI optical switch has three output ports with low crosstalk among eight output ports [16]. In addition, we have reported that a 4-stage nested MZI switch has low crosstalk less than −40 dB over a wavelength range of as wide as 200 nm from 1450 to 1650 nm by choosing six ports among 16 output ports [18].…”
Section: Introductionmentioning
confidence: 98%
“…Crosstalk of the nested MZI optical switch as well as the conventional MZI optical switch becomes larger when the input signal wavelength deviates from an optimal wavelength because both the coupling ratio of the DC and the phase given by the arm waveguides vary as wavelength. To mitigate this wavelength dependence, a previous study [16] proposed a nested MZI optical switch employing phase generating couplers (PGCs) [17] in place of DCs. PGCs create the phase to cancel the wavelength dependence of the arm waveguides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Mach-Zander interferometer can be simulated using FDTD while it consists of an optical y-splitter and a y-combiner waveguide. In [19] the bending radius of Y waveguides at 385 µm and the average free spectral range (FSRs) of 18 nm are optimized for the MZI model. Also, a MZI can be used as an optical switch.…”
Section: Introductionmentioning
confidence: 99%
“…A wavelength selective filter (WSF) has become an essential device in a wavelengthdivision-multiplexed (WDM) optical fiber communication system, where multiple color signals are transmitted in parallel in the optical fiber to increase communication throughput [1][2][3][4]. Current systems employ wavelengths between 1.3 and 1.6 µm as optical fibers show the smallest absorption and the smallest chromatic dispersion near these wavelengths.…”
Section: Introductionmentioning
confidence: 99%